PEMANFAATAN LINGKUNGAN SEKITAR SEKOLAH DALAM MENUMBUHKAN SIKAP PEDULI SOSIAL SISWA SEKOLAH DASAR DI TENGAH TANTANGAN GLOBALISASI UNTUK MENDUKUNG SDGS 4 SEBAGAI PEMBELAJARAN IPS - Priyono Tri Febrianto; Ricca Aulia Rahma; Mafrichatuz Zuhroh; Putri Faridatus Sholeha; Sayyidati Beta Masbaha Azzahroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary education in Indonesia faces challenges in the globalization era, particularly in maintaining students’ social awareness and local values. Social Studies (IPS) plays an important role in developing students’ social character, yet its implementation is often conventional and less contextual. This study aims to examine the utilization of the school environment as a learning resource in Social Studies to foster social care attitudes among elementary school students in supporting Sustainable Development Goals (SDGs) point 4 on quality education. This research employed a qualitative descriptive approach using a literature study method. Data were collected from scientific journals, books, and relevant previous studies and analyzed through content analysis techniques. The results show that environment-based Social Studies learning enhances students’ engagement, understanding of social concepts, learning motivation, and social care attitudes. Learning activities that utilize the surrounding environment provide concrete and meaningful experiences through direct interaction with real social phenomena. Therefore, the use of the school environment as a learning resource is an effective strategy to improve the quality of Social Studies learning and support quality education in line with SDGs 4.